Pengaruh Self-Assessment Good Corporate Governance Terhadap Return On Asset (Roa) Pada Sektor Perbankan Syariah Yang Terdaftar Di Bei 2015-2022 - latifah, latifah; Nasution, Dinda Pradina; Mingka, Asrawi Fahmi; Iqbal, M. (JPSDa: Jurnal Perbankan Syariah Darussalam, 2024)
This research was conducted to analyze the influence of self-assessment good corporate governance on return on assets in the sharia banking sector listed on the IDX 2015-2022. This research uses a quantitative type of research with a descriptive approach. The sample used in this research was a saturated sampling technique. Self-assessment data on good corporate governance and return on assets in the sharia banking sector listed on the IDX for the 2015-2022 period were used as samples with a sample size of 31 samples. The data in this study were analyzed using computer software, namely the IBM SPSS Statistics 26 application program. The results of the research show that self-assessment of good corporate governance has a negative relationship and has a significant effect on return on assets in the sharia banking sector listed on the BEI for the 2015-2022 period. This is known from the calculated t-coefficient, namely -4.178 with a sig-t value of 0.000 < 0.05.